2021
DOI: 10.14814/phy2.14705
|View full text |Cite
|
Sign up to set email alerts
|

Greater increase in internal carotid artery shear rate during aerobic interval compared to continuous exercise in healthy adult men

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It may be reasonable to presume that acute exercise that improves cognitive function can maintain chronic cognitive health through repeated performance. However, it is not fully understood how the acute effects of exercise on cognitive function determine chronic effects (Hashimoto et al, 2021), and thus caution is warranted in estimating the chronic effects from the present results.…”
Section: Discussionmentioning
confidence: 92%
“…It may be reasonable to presume that acute exercise that improves cognitive function can maintain chronic cognitive health through repeated performance. However, it is not fully understood how the acute effects of exercise on cognitive function determine chronic effects (Hashimoto et al, 2021), and thus caution is warranted in estimating the chronic effects from the present results.…”
Section: Discussionmentioning
confidence: 92%
“…The Journal of Physiological Sciences cerebral SR more effectively than continuous steady-state exercise [8]. Therefore, the improvement of EF may be dictated or subject to regulation by the specific flow/SR 'phenotype' .…”
Section: Open Accessmentioning
confidence: 99%
“…This is surprising, given the controversial findings relating to systemic flow-mediated dilation (FMD) in hypoxia [12][13][14][15][16][17][18][19][20][21][22] combined with the observation that retrograde flow is confined to the systemic and not the cerebral arterial circulation [11,23,24]. Specifically, the increase in retrograde flow [22,25,26], known to attenuate systemic EF [27], given its absence in the cerebral circulation [8,23,24,28] would result in preserved (i.e., maintained) EF.…”
Section: Open Accessmentioning
confidence: 99%
“…While this evidence has emerged mainly from studies of the forearm artery [ 104 ], it is reasonable to infer that greater shear stress and therefore vascular adaptation, would also occur in the cerebral vasculature. Indeed, Ogoh et al [ 121 ] showed significantly higher internal carotid artery velocity (i.e., shear stress) for HIIT compared with MICT during acute exercise and recovery. Moreover, Klein et al [ 122 ] found significantly greater total MCAv (i.e., shear stress) during an acute bout of HIIT compared with MICT for younger and older adults.…”
Section: Is There Rationale For Higher Intensity Exercise?mentioning
confidence: 99%
“…Therefore, exercise at higher intensities seemed counterintuitive to increasing CBF and shear stress within the cerebral circulation [ 124 ]. However, combining intervals of high intensity exercise with short intervals of active recovery (i.e., HIIT) appears to lead to a greater accumulation of CBF and shear stress than MICT [ 121 , 122 ]. Furthermore, studies examining MCAv during rowing exercise [ 125 ] and running [ 126 ] have shown that MCAv may not exhibit the same inverted U-shape pattern as cycling exercise.…”
Section: Is There Rationale For Higher Intensity Exercise?mentioning
confidence: 99%